Perencanaan pada manajemen pembelajaran projek penguatan profil pelajar pancasila tema kearifan lokal di sekolah dasar - Putri Rahma Zulaikha; Sri Marmoah Marmoah; Tri Budiharto Budiharto (Didaktika Dwija Indria, 2025)
This research aims to describe planning for the learning management project to strengthen the profile of Pancasila students with the theme of local wisdom at SD Negeri 1 Bulukerto. This research is qualitative research with a case study method. Data collection techniques in this research used observation, interviews and document study. The subjects in this research were the fourth grade students, the fourth grade teacher, and the school principal. The technique for testing the validity of this research uses triangulation of techniques and sources. This research data analysis uses the Miles and Huberman model data analysis. The research results show that planning for the learning management project for strengthening the Pancasila student profile consists of several stages, namely understanding the meaning of the project for strengthening the Pancasila student profile, preparing the educational unit ecosystem, facilities and infrastructure, and designing the project for strengthening the Pancasila student profile.